Instrumentalisme Nilai-Nilai Spiritualitas, Kejujuran, dan Amanah dalam Pengembangan Pendidikan - Muttaqin, Jamalul (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
Education is the heart of civilization that must have a spirit to stay alive to develop to contribute to the advancement of Indonesian education. This article tries to examine the instrumentalism of spirituality values that are integrated with honesty and trust in the development of education in Indonesia. This research uses a qualitative approach. Sources of data obtained from several books, journals, articles and other scientific works. Research findings illustrate that ma'rifatullah's spiritual values can be implemented in the world of education. Second, it embodies the values of honesty and trustworthiness as a pattern of educational management. This research found the development of ma'rifatullah's spiritual values, honesty, and trust as the key in developing the world of mtakahir education.